THE CONCEPT OF CHILDREN'S MORAL EDUCATION IN THE PERSPECTIVE OF THE HADITH OF THE PROPHET MUHAMMAD ﷺ - Muh Alief Sabil; Romlah Abubakar Askar; Miftahuddin (STMIK Indonesia Banda Aceh, 2026)
Moral education for children is the primary foundation for character development for the Muslim generation . Amidst increasingly rapid technological developments and social change , various moral issues in children present challenges that require serious attention . Hadith of the Prophet Muhammad ﷺ As a source of Islamic teachings after the Qur'an, it provides comprehensive guidelines for educating children to have noble morals . This study aims to analyze the concept of children's moral education from the perspective of the hadith of the Prophet Muhammad ﷺ . and its relevance in modern life . The study used a library research method with a thematic hadith study approach ( maudhu'i ). Primary data sources came from hadith books , while secondary data sources were obtained from books , hadith commentary books , and relevant scientific articles . The results of the study show that children's moral education in the hadith is built on the principles of compassion , exemplary behavior , habituation of worship, instilling good manners, and moral responsibility . These principles complement each other in shaping children's character with noble morals and remain relevant to be applied in facing moral challenges in the digital era.